Macrophages and Epithelial Cells Respond Differently to the Pseudomonas aeruginosa Type III Secretion System - Coburn, Jenifer (American Society for Microbiology, 1999)
The multiple effects of Pseudomonas aeruginosa type III secretion have largely been attributed to variations in cytotoxin expression between strains. Here we show that the target cell type is also important. While lung epithelial cells showed significant changes in morphology but not viability when infected with P. aeruginosa, macrophages were efficiently killed by P. aeruginosa. Both responses were dependent on the type III secretion system.